Diretrizes para construção de políticas de acesso e permanência para programas de pós-graduação : o caso UFSCar - Lucifora, Leonardo de Souza e Silva (2017)
The main objective of this research was to construct guidelines for a future formulation of policies of access and permanence for students from disadvantaged economic sectors, based on the current legislation, that intend to enter in the courses of master academic and doctorate. This was done through the collection of information on the lattes platform and on institutional sites, both of free access, and also through questionnaires applied to undergraduate and graduate coordinators. It was also part of this objective to verify what are the current institutional policies geared specifically to graduate students. Finally, the following proposals for guidelines for actions for access were elaborated: a) Increased dissemination of UFSCar's research groups to motivate undergraduate students to join these groups; b) Offer of language courses for UFSCar undergraduates who wish to enter the master's and doctoral courses; c) Assistance in the elaboration of research projects, both at the undergraduate level (CI projects) and at the postgraduate level (Master's projects, mainly). Actions for permanence: d) Improvement of UFSCar infrastructure to meet people with special needs; e) Encouraging the active participation of postgraduate students in the discussions involving scholarship, housing, food and transportation; f) Expand the offer of scholarships that take into account socio-economic criteria, in addition to the academic criteria. For both of them: g) To create spaces for discussion at UFSCar that deal with the problems of access and permanence in postgraduate courses of students from economically disadvantaged social strata, involving teaching staff, technical-administrative staff, undergraduate students and graduate students.